The effect of aluminum interlayer on weld strength, microstructure analysis, and welding parameters optimization in resistance spot welding of stainless steel 316L and Ti6Al4V titanium alloy - Taufiqurrahman, I. (Growing Science, 2022)
Stainless steel (SS) and Titanium alloy (Ti) are the most commonly used materials in many industrial fields such as the automotive and aerospace industry. Stainless steel has good corrosion resistance and titanium alloy has an extremely lightweight characteristic. The combination of both materials has become a tremendous innovation in the industrial sector. Resistance spot welding which has commonly applied in many industrial fields is a good consideration to join these two dissimilar materials due to the high efficiency that could be achieved by using this method. However, the way of joining these dissimilar materials should be carefully considered due to the significant difference in mechanical properties between SS and Ti. In the present study, 3 mm of SS316L and Ti6Al4V sheets were joint under the resistance spot welding method with an aluminum interlayer. The optimized welding parameters were provided under the Taguchi method L9 orthogonal array along with the mechanical propertiesâ investigation. The optimum welding parameters were 11 kA of weld current, 30 Cycles of welding time, and 5 kN of electrode force which produced 8.83 kN tensile-shear load of the joint. The mechanical structure analysis shows the different morphology between stainless steel and titanium interfaces and the intermetallic compound layer was formed on the SS/Al and Al/Ti interfaces. The EDX analysis shows the atomic diffusion-reaction on the application of aluminum as an interlayer on the SS/Ti joint. Â© 2022 Growing Science Ltd. All rights reserved.